Deriving a Cortisol-Related Stress Indicator From Wearable Skin Conductance Measurements: Quantitative Model & Experimental Validation - Westerink, Joyce H. D. M.; Rajae-Joordens, Roos J. E.; Ouwerkerk, Martin; van Dooren, Marieke; Jelfs, Sam; Denissen, Ad J. M.; Penning de Vries, Eric; van Ee, Raymond (Frontiers in Computer Science, 2020)
In order to find a stress indicator that can be used to monitor stress with wearables, we compare the almost instantaneous effects of psychological stress on skin conductance, with the effects on the stress hormone cortisol, peaking about 20-30 min later. We modelled this relation deploying a convolution of the height of the skin conductance peaks with the cortisol stress response curve, and used it to determine a skin conductance-derived estimate of stress-induced cortisol. We then conducted a first experiment to validate this model, comparing the stress-induced cortisol estimates with cortisol as measured in saliva samples. Participants (N=46) completed stressful, boring, and performance tasks in a controlled laboratory setting. Salivary cortisol samples were taken at regular moments. Based upon the pattern of measured salivary cortisol before and after the performed stressful task we divided subjects in high-cortisol responders and low-cortisol responders. For both groups, we found substantial correlations between the skin conductance-based stress-induced cortisol estimates and the measured salivary cortisol. In addition, the (Fisher-corrected) mean within-participant correlation between these variables was found to be 0.48 which proved to be significantly different from zero. These findings support the use of the skin conductance-based stress-induced cortisol estimates as a stress indicator reflecting in-body cortisol levels.